1993
DOI: 10.1002/apmc.1993.052060115
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluß des Photoinitiators auf die radikalische Härtung von Siliconacrylaten, 9

Abstract: ZUSAMMENFASSUNGDie photoinduzierte radikalische Vernetzung von Siliconacrylaten wurde mit verschiedenen Photoinitiatoren vom Benzoyltyp untersucht. Die Photovernetzung derartiger Produkte kann mit Hilfe eines radikalischen Kettenprozesses beschrieben werden. Aus kalorimetrischen Messungen folgt, da8 Sauerstoff den KettenprozeB inhibiert und terminiert, wobei die Vernetzungsgeschwindigkeit und die Inhibierungszeit Funktionen des Luftdrucks, der Lichtintensitat und der Quantenausbeute der Initiatorphotolyse sind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The initiator 1-hydroxycyclohexyl phenyl ketone (HPK) (Aldrich) was used as received. HPK has a quantum yield of photolysis of Φ = 1, and it yields clear cured films of poly(dimethyl acrylates) and polyesters . The concentration of the initiator, c HPK , in the MAOP-DMS films varied from 0.25 to 5.0 wt %.…”
Section: Methodsmentioning
confidence: 99%
“…The initiator 1-hydroxycyclohexyl phenyl ketone (HPK) (Aldrich) was used as received. HPK has a quantum yield of photolysis of Φ = 1, and it yields clear cured films of poly(dimethyl acrylates) and polyesters . The concentration of the initiator, c HPK , in the MAOP-DMS films varied from 0.25 to 5.0 wt %.…”
Section: Methodsmentioning
confidence: 99%
“…The initiation quantum yield of BDK was reported to be 0.52. [22][23][24][25] In Figure 6, the values of t i which were calculated from the oxygen solubilities are plotted vs. the experimental data from RT-FTIR spectroscopy which were taken from Figure 4. From the close correlation between the both sets of data it can be concluded that the decay of the induction period with increasing temperature is solely due to the decreasing oxygen solubility in the acrylate.…”
Section: Resultsmentioning
confidence: 99%
“…[17a] Acrylates are arguably the most popular cross-linkers for free-radical photo-curingo fs ilicone formulations. [32] Their main advantages are high reaction rates, solvent-free conditions, ambient temperature operation, and high spatial resolution, whereas their biggest disadvantage is oxygen inhibition, which may lead to tackiness and poor structural proper-ties. [33] The oxygen level in at ypical industrialc oating line shouldb eb elow 50 ppm.…”
Section: Photoinitiatedc Uringmentioning
confidence: 99%
“…By irradiation with UV‐light or low‐energy electron beams (EB), polysiloxane chains containing reactive functionalities such as epoxide ( 7 ), acrylate ( 8 ), thiol ( 9 ), and vinyl ( 10 ; Scheme ) can be cross‐linked by free‐radical or cationic polymerization mechanisms . Acrylates are arguably the most popular cross‐linkers for free‐radical photo‐curing of silicone formulations . Their main advantages are high reaction rates, solvent‐free conditions, ambient temperature operation, and high spatial resolution, whereas their biggest disadvantage is oxygen inhibition, which may lead to tackiness and poor structural properties .…”
Section: Curing Systems (Cross‐linking Reactions)mentioning
confidence: 99%